Jawabanmu

2014-01-25T11:42:31+07:00
2-3x = 3x+4
-6x = 2
x   = -2/6
x  = -1/3

x+2= x2 +4x
-x2 - 3x + 2 = 0 dikali -1 agar -x2 menjadi positif
x2 + 3x - 2 = 0
 tidak ketemu jawabannya

f(2-3x) = 3x + 4
f(2-3x) = -(-3x+2)+6
f(2-3x) = -(2-3x)+6
f(x) = -x+6

f(x+2) = x^2 + 4x
f(x+2) = x^2 + 4x + 4 - 4
f(x+2) = (x+2)^2 -4
f(x) = x^2 -4
2014-01-25T11:56:52+07:00
F(2-3x) = 3x + 4
f(2-3x) = -(-3x+2)+6
f(2-3x) = -(2-3x)+6
f(x) = -x+6

f(x+2) = x^2 + 4x
f(x+2) = x^2 + 4x + 4 - 4
f(x+2) = (x+2)^2 -4
f(x)     = x^2 -4

dari kak reanind nih
1 5 1